2016
DOI: 10.3892/ijo.2016.3479
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin induces apoptosis through the mitochondrial pathway in human gastric cancer SGC-7901 cells

Abstract: Abstract.Oridonin is one of the most important antitumor active ingredients of Rabdosia rubescens. Recently published studies from our laboratory have demonstrated that oridonin was able to arrest human gastric cancer SGC-7901 cells at G 2 /M phase. However, little is known about inducing apoptosis in gastric cancer. The aim of this study was to investigate the effect of oridonin on antineoplastic capability of SGC-7901 cells and the detailed molecular mechanism of oridoninmediated intrinsic pathway of apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Antimetastatic activity of oridonin was further confirmed in a xenograft zebrafish model tested at a dose of 8 mg/kg that showed significant effect (p < 0.01) in comparison to the vehicle control group [24]. Gao et al (2016) reported that oridonin induced apoptosis by downmodulating the expression level of B-cell lymphoma 2 (BCL-2), but upmodulating the expression of BAX, thus reducing the BCL-2/BAX ratio in human gastric cancer SGC-7901 cells. Moreover, oridonin treatment activated caspase-3 by promoting the release of cytochrome c from mitochondria to the cytosol [27].…”
Section: Oridoninmentioning
confidence: 90%
See 2 more Smart Citations
“…Antimetastatic activity of oridonin was further confirmed in a xenograft zebrafish model tested at a dose of 8 mg/kg that showed significant effect (p < 0.01) in comparison to the vehicle control group [24]. Gao et al (2016) reported that oridonin induced apoptosis by downmodulating the expression level of B-cell lymphoma 2 (BCL-2), but upmodulating the expression of BAX, thus reducing the BCL-2/BAX ratio in human gastric cancer SGC-7901 cells. Moreover, oridonin treatment activated caspase-3 by promoting the release of cytochrome c from mitochondria to the cytosol [27].…”
Section: Oridoninmentioning
confidence: 90%
“…A wide variety of sources have reported the anticancer mechanism of oridonin in multiple cancer cell lines [17,24,27,[29][30][31][32]. According to the study of Yao et al (2017) oridonin induced autophagy by decreasing the protein levels of glucose transporter 1 (GLUT1) and monocarboxylate transporter 1 (MCT1) in SW480 human colorectal cancer cells, in the BALB/c xenograft model.…”
Section: Oridoninmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by some recent studies, some traditional Chinese medicines have been identified as effective anticancer drugs for various cancers ; however, the specific protective mechanisms of different herbal medicines are not the same. R rubescens has been used in traditional Chinese medicine for oesophageal cancer treatment in China for a long time . Oridonin, one of the most important active ingredients of R rubescens , was revealed to have a potential therapeutic effect against the migration of four selected cancer cell lines (MGC‐803, MCF‐7, PC‐3 and Eca‐109 cells) ; however, the effect of oridonin on the H1688 SCLC cell line had not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the mitochondrial redox change is proved to be a potential mediator for the pro-apoptosis effect of oridonin [565]. The anti-proliferative effect of oridonin is also shown to be associated with mitochondrial-mediated apoptosis, which is characterized by mitochondrial membrane potential reduction, subsequent cytochrome c release, PARP, caspase-3 and -9 activation, and decreased Bcl-2/Bax ratio [551,565,574,575]. Oridonin also inhibits cell proliferation through bone morphogenetic protein 7 (BMP7)/p38 MAPK/ p53 pathway in human colorectal cancer HCT-116 and SW-620 cells [553,576,577], and induces apoptosis via hydrogen peroxide (H 2 O 2 ) production and glutathione depletion in human colorectal cancer SW-1116 cells [578].…”
Section: Oridoninmentioning
confidence: 99%